2013
DOI: 10.1111/ijfs.12379
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic loads on stability of various chlorine‐based sanitisers

Abstract: This study examined the effect of pH of chlorine-based sanitisers on the reaction of free chlorine with compounds present in a variety of food environments. A model food system was first used to determine chlorine reactions with individual organic compounds. Different classes of organic compounds were added to chlorinated water at three different pHs (2.5, 6.0 and 9.3). Free and total chlorine concentrations were recorded in each sample by titrimetric assay. The results show that the level of free chlorine los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…However, for RW, alternative technologies to chlorine must be used due to the instability of chlorine and the adverse effects of by-product formation in the presence of organic matter (G omez-L opez, Marín, Medina-Martínez, Gil, & Allende, 2013;Van Haute, Sampers, Holvoet, & Uyttendaele, 2013;Waters & Hung, 2014). Among these alternatives, peroxyacetic acid (PAA) and Citrox ® (a mix of organic acids and phenolic compounds, OA/ PC), inactivate Escherichia coli in PWW without by-product formation and with lower pH dependence (Kitis, 2004;).…”
Section: Introductionmentioning
confidence: 99%
“…However, for RW, alternative technologies to chlorine must be used due to the instability of chlorine and the adverse effects of by-product formation in the presence of organic matter (G omez-L opez, Marín, Medina-Martínez, Gil, & Allende, 2013;Van Haute, Sampers, Holvoet, & Uyttendaele, 2013;Waters & Hung, 2014). Among these alternatives, peroxyacetic acid (PAA) and Citrox ® (a mix of organic acids and phenolic compounds, OA/ PC), inactivate Escherichia coli in PWW without by-product formation and with lower pH dependence (Kitis, 2004;).…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, tryptone had more effect on NEO than AEO. Many studies also reported that free chlorine reacts with organic matter and, as a consequence, the antimicrobial ability decreased (Ayebah et al, 2006;Waters & Hung, 2014). Many studies reported that when a purified and dispersed virus was subjected to chlorine disinfection treatment, very low Ct values (free chlorine concentration times contact time) are necessary to inactivate noroviruses (Cromeans, Kahler, & Hill, 2010;Grabow, Gauss-Muller, Prozesky, & Deinhardt, 1983;Shin & Sobsey, 2008;Thurston-Enriquez, Haas, Jacangelo, & Gerba, 2003).…”
Section: Impact Of Tryptone On Eo Water Disinfection Of Mnv-1 and Havmentioning
confidence: 99%
“…The presence of organic matter is an inevitable part of food and food processing environment. Many studies showed that organic matter reacted with the free chlorine in EO water and hence reduced the effect of inactivation (Ayebah, Hung, Kim, & Frank, 2006;Waters & Hung, 2014). For example, when chicken serum was added to AEO, the free chlorine in EO water decreased quickly (Ayebah et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Composition of the process water is an important factor in FC loss. Protein and phenolic compounds cause significant chlorine loss of chlorinated water, whereas carbohydrates, fat, and mineral have no significant effect on chlorine loss (Waters and Hung 2014). Prevention of pathogen survival in chlorinated process water can be achieved by maintaining sufficient FC concentration at all times.…”
Section: Chlorine Supremacymentioning
confidence: 99%
“…Recent studies have also demonstrated that the presence of THMs in process water does not affect the wholesomeness of the end product At high pH, chlorine reacts with organic nitrogen-based materials to produce chloramines. Waters and Hung (2014) measured the THM reaction products from chlorinated water at different pH with resorcinol. They found chloroform accounts for the largest percentage of THMs detected in all samples (>99 %), indicating that it is the main THM product when chlorine reacts with organic materials.…”
Section: Chlorine Supremacymentioning
confidence: 99%